Characteristics of nurses with musculoskeletal disorders from Dr Soedarso Regional Hospital, Pontianak, Indonesia - Wuriani Wuriani; Annisa Rahmawati; Ardi Wahyudi; Sunandar Syahlewangi; Dian Saputri; Jaka Pradika; Almumtahanah Almumtahanah; Ridha Mardiyanti; Uji Kawuryan; Suriadi Jais (PAGEPress Publications, 2024)
Musculoskeletal disorders (MSDs) can have a significant negative impact on quality of life, resulting in reduced ability to work, absenteeism, and possibly switching occupations. The purpose of this study was to investigate the relationship between the prevalence and severity of MSDs and the nurse characteristics (NCs) of nurses working in the Dr Soedarso Regional Hospital (DSRH) inpatient department. An analytical and descriptive cross-sectional methodology was used to examine 134 nurses from Inpatient Wards A and B. Total sampling was used to select the respondents. The level of exposure to the conditions investigated by the quick exposure check (QEC), namely, static and dynamic movements in the back, shoulders/arms, neck, and work-related stress, was significantly correlated with gender and neck (0.050), a history of education-related physical strain, such as back mobility (0.021), years of work-related strain on the neck (0.040), and work-related stress (0.033). There were no significant correlations found between age and static and dynamic movements of the back, shoulders/arms, and neck. Gender, education level, and employment duration all have a strong correlation with MSDs among DSRH inpatient nurses.